Study the relationship between organizational commitment, perceived organizational support and turnover intention in Celestica Johor, Malaysia. - Hasan, Siti Amrah (2011)
Examining the associations between organizational commitment, Perceived Organizational Support and turnover intention among employees in Celestica, Johor was the purpose of this study. Since there is so many employees in Celestica tend to leave the organization, so this study will evaluate and find why is this happened and why some of them tend to stay with Celestica. Based on the extant literature on Organizational Commitment, Perceived Organizational Support and turnover intention, this study proposed hypothesized associations between organizational commitment, perceived organizational support and turnover intention in Celestica, Johor. Organizational commitment consists of three which is affective commitment (AC), continuance commitment (CC) and normative commitment (NC). But, only affective commitment (AC) and continuance commitment (CC) will be as independent variable in this study. Normative commitment (NC) will not be include in this study because according to (Perryer et al.., 2010) there already been done extensively by the aforementioned authors and many others. Data was collected from selected employees who work in Celestica Johor at Jalan Bayu (B1), Jalan Hasil (B2) and Jalan Tara (B3).